Freire: vigente e inspirador en la alfabetización de personas adultas - Barboza Araya, Roberth; Camacho Varela, Samantha; Flores Davis, Luz Emilia; Hernández Segura, Ana María; Vargas Alpízar, María Goretti; Venegas Ugalde, Jeimmy (Revista Electrónica Educare, 2008)
This article presents diverse experiences regarding alphabetization of grown-ups, inspired by Paulo Freire’s ideas. The validity of Freire’s contributions are reconstructed through an integrated academic work, carried out in different contexts, through the coordination between the National University (Universidad Nacional) and the Costa Rica Electricity Board (Instituto Costarricense de Electricidad), with the aid of professionals and students.